Motivation factors on trampoline activity / Noor Zuriati Ahmad Zalilah - Ahmad Zalilah, Noor Zuriati (Faculty Of Sports Science And Recreation, 2019)
Motivation can be defined as the psychological that lead an individual to behave in a certain manner, which drive one to behave like that or makes one enthusiastic about performing a task. This study is aimed to determine the type of motivation factor which consist of 'success/status', 'fitness/skill', 'extrinsic reward', 'team', ;friendship/fun', 'energy release'. The purpose of this study to identify whether these six variable that have significant different motivation type between genders participate in trampoline activity and the type of motivation factor those participate on trampoline activity. The participant involved (n=170) that using convenience sampling. The instrumentation that used on this study was Participation Motivation Questionnaire (PMQ). On this study used for analyse the data was Independent T-Test for analyse the significant different between gender. While, the descriptive analysis used to determine the gender, age, race and frequency of demographic factor. Based on Independent T-test shown extrinsic reward whereas p value is (0.10 = p<0.05) was significant between others factors. Hence, this study was show participant on trampoline activity to play trampoline because of the external factor.